IMPERATIVE FEATURES IN ARABIC TEXTBOOK FOR MADRASAH ALIYAH: REPRESENTATION AND LEARNING IMPLICATIONS - Mukminin, Muhamad Saiful; Sitorismi, Aninda Ayu; Atikoh, Iklilah; Irianti, Waviq Alfiana (Al-Katib: Jurnal Pendidikan Bahasa Arab, 2024)
This study uses a descriptive qualitative research method with content analysis on the Arabic language textbook for Madrasah Aliyah. The purpose of this study is to analyze the use of imperative features in the form of imperative verbs and their implications for learning. Data were collected through direct observation of relevant sentences, focusing on identifying forms of imperative verbs in patterns such as tsulatsi mujarrad, tsulatsi mazid, ruba'i mujarrad, and ruba'i mazid. Each imperative verb form found was analyzed to identify its morphological patterns and semantic meanings within the context of Arabic language learning. The data analysis techniques include morphological analysis to determine the transformation from regular verbs to imperative verbs, as well as semantic analysis to understand the meaning of each imperative verb in its sentence. The research results indicate that the use of imperative verbs in the Arabic language textbook includes various wazan patterns and is used to give clear instructions to students within the learning context. The learning implications of using imperative verbs are related to the application of learning theories, such as social learning theory, cognitive theory, and task-based learning, which support students' understanding of language structure and its application in everyday communication.